ISLAM-KRISTEN DI “KOTA KALONG”: BEST PRACTICE PEMBANGUNAN RUMAH IBADAT BERBASIS KEARIFAN LOKAL - Muhammad Irfan Syuhudi; Nensia (Harmoni, 2021)
Rejection and destruction of a certain house of worship are often found in various regions in Indonesia, especially after the issuance of PBM Numbers 9 and 8 of 2006. Generally, when a house of worship of the religious minority group is to be built, the majority tends to carry out rejection and destruction. This article aims to describe the best practices for building houses of worship in Soppeng Regency as well as local wisdom related to the construction of houses of worship. Using this type of qualitative research, data collection was carried out through interviews, observations, and literature studies, and analyzed descriptively-qualitatively. Informants included Muslim and Christian religious leaders, Soppeng Regency FKUB, Soppeng MUI, and the community. This study found: (1) There has never been a case of rejection and destruction of a house of worship in Soppeng. Although all churches were established long before the publication of PBM Numbers 9 and 8 of 2006, Muslims until now have never questioned the renovation of the church. Since it was first built, all churches in Soppeng have undergone several renovations. In addition, Muslims have never questioned the location of the church, which stands in the middle of a Muslim settlement; (2) One of the causes of harmonious relations between Muslims and Christians is brotherhood and kinship. Until now, the Soppeng Bugis still have siblings and relatives of different religions, and some of them live in harmony living under the same roof. Also, the people uphold the local wisdom inherited from their parents, Iyassi Soppengngi, Soppeng Belongs to Us Together.